Hadis dan Media Sosial sebagai Alat Da’wah di Instagram: Study Ilmu Hadis - Siddik Firmansyah; Marisa Rizki (IAIN Batusangkar, 2023)
Social media that requires a network makes a new life for its users in the current millennial era. The purpose of this study is to see the study of hadith in social media used as a tool of da'wah in Islam, the research methodology uses descriptive analysis. The study of hadith in Instagram as a social media is used as a connector for Islamic da'wah. The results in this study are divided into three categories. First, the delivery of the hadith only includes a translation without showing the original editorial which is claimed to be from the prophet, after examining the accounts of Islamic studies, there are actually many hadiths that are not in accordance with the history and make false hadiths. Second, conveying the hadith by including the source of the hadith but leading to other sources so that the true meaning of the hadith as da'wah is used for worldly purposes. Third, conveying hadith in social media purely because of Allah and setting the hadith of the prophet in its place so that the truth of da'wah is conveyed to people who see it in the media. Therefore in taking news in the media must be careful to see the truth.